A Classification for Syndesmosis Injuries Based on Soft Tissue and Bony Anatomy - Diogo Vieira Cardoso MD; Andrea Veljkovic MD, MPH, BComm, FRCSC; Silvia Valisena MD; Thibault Favre MD; Peter Salat MD; Sana Boudabbous MD; Kevin Wing MD, FRCSC; Murray J. Penner MD, FRCSC; Alastair S.E. Younger MB ChB, ChM, FRCSC (Foot & Ankle Orthopaedics)
Category: Trauma; Ankle Introduction/Purpose: Syndesmosis injuries result in potential separation to the intimate distal tibial and fibular connection/articulation and can result in meaningful ongoing disability and the development of early post-traumatic arthritis. The injury pattern includes ligament injuries, cartilage damage, and/or fractures. These injury patterns may predicate outcomes. The associated fractures and ligament injuries may also determine the nature of fixation and management required. While classification exists for posterior malleolar, fibular, and ankle fractures, no systematic approach exists for the classification and treatment of syndesmosis injuries. This study aims to describe a comprehensive classification system for syndesmosis injuries and determine its validity. Methods: Descriptive system: The ankle was divided into five zones based on bony and soft tissue anatomic locations: lateral (L), medial (M), posterior (P), anterior (A), and intraarticular (I). In each location no injury is type 0, soft tissue/avulsion injury type 1, and boney injury type 2. (Figure 1). Study group: Patients with operative syndesmosis injuries in a single institution between January 2002 and December 2012 were reviewed. Injury patterns were classified by 3 experts, 2 semi-experts, and 2 musculoskeletal radiologists based on orthogonal anteroposterior and lateral radiographs. Statistical analysis: A 103-patient cohort was deemed to be sufficient based on power analysis Weighted kappa statistics with quadratic weights was used for test retest analysis. For inter-rater reliability, a separate analysis was completed for experts, semi-experts, and radiologists. Intraclass correlation coefficients were obtained. Results: All injuries could be classified according to the proposed classification. The most frequent pattern was the type B221 (13%) and C221 (12%). The interobserver agreement among all observers was excellent for the medial (ICC of 0.847) and lateral aspect (ICC of 0.762), good for the posterior aspect (ICC of 0.615), and poor for the anterior aspect (ICC of 0.233) (Table 1). The classification showed good to excellent intraobserver agreement except for the anterior aspect, which had poor agreement for the semi-expert raters (Table2). Conclusion: The syndesmosis classification is a valid system to represent the complexity of injuries that may occur. Inter- and intraobserver agreement among raters with different levels of expertise in classifying injuries based only on X-ray was good to excellent, with the exception of the anterior aspect which may require additional imaging techniques for proper classification. The categorization of different injuries by their location allows for a better understanding of how injurie presents. It should lead to improved research outcomes and communication between professionals regarding injury patterns and potential treatments in the future, as not all syndesmosis injuries are the same.